Retropsective discussion (Scottish Historical and Archaeological Internet Reports, 2009)
Scotland's First Settlers has been very successful not only at providing information relating to its primary aim, that of looking at the Mesolithic settlement of the Inner Sound, but also at filling out the picture of human activity in the Inner Sound up to the present day. The midden site at the rockshelter of Sand has proved to be one of the earliest midden sites in Scotland, yielding a wealth of information on the material culture, activities and environment of its inhabitants. Other Mesolithic sites broadened the picture. Yet more sites yielded information right up to the present day and they provide a formidable database which we hope will play an important role in future studies of human settlement in the area.